2000
DOI: 10.3171/spi.2000.93.1.0071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cervical spinal cord stimulation on cerebral blood flow in the rat

Abstract: Object. Spinal cord stimulation (SCS) is frequently used for the treatment of chronic pain. Although the mechanisms by which SCS alleviates pain are unclear, they are believed to involve changes within the dorsal horn of the spinal cord. Spinal cord stimulation has also been found to cause significant vasodilation in the peripheral vasculature. The mechanisms underlying this effect are thought to involve sympathetic blockade. A rostral vasodilatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…Intravenous administration of hexamethonium (10 mg/Kg) prior to the initiation of cSCS in the rats abolished the cSCS-induced cerebral vasodilation (Sagher et al, 2000). Another study also showed that cSCS-induced cerebral vasodilation was abolished by both a high-dose of hexamethonium (20 mg/Kg) and prazosin (a selective α-1 receptor blocker, 1 mg/Kg) (Patel et al, 2003).…”
Section: Animal Models and Experimental Designs-mentioning
confidence: 95%
See 4 more Smart Citations
“…Intravenous administration of hexamethonium (10 mg/Kg) prior to the initiation of cSCS in the rats abolished the cSCS-induced cerebral vasodilation (Sagher et al, 2000). Another study also showed that cSCS-induced cerebral vasodilation was abolished by both a high-dose of hexamethonium (20 mg/Kg) and prazosin (a selective α-1 receptor blocker, 1 mg/Kg) (Patel et al, 2003).…”
Section: Animal Models and Experimental Designs-mentioning
confidence: 95%
“…Effects of cSCS on the cerebral vascular system include an increase in CBF (Meglio et al, 1991 a;Ebel et al, 2001;Robaina et al, 2004;Karadag et al, 2005) combined with a decrease in cerebral vascular resistance and an increase in blood flow velocity (Meglio et al, 1991 b), leading to an enhancement of the local-regional delivery of oxygen (Clavo et al, 2002(Clavo et al, , 2003, Further effects of cSCS on the cerebral vascular system also include a decrease in induced vasospasms Gurelik et al, 2005) and an improvement of neurological dysfunction , a modification of glucose metabolism (Momose et al, 1989;Clavo et al, 2006), and the prevention of early spasm due to subarachnoid hemorrhage (SAH) . cSCS effects on cerebral vasodilation depend on a decrease of sympathetic tone (Sagher et al, 2000;Patel et al, 2003), activation of vasomotor centers (Sagher et al, 2000;Patel et al, 2004) and release of neurohumoral factors (Hosobuchi, 1985;Goksel et al, 2001). …”
Section: Effects Of Scs On Cerebral Vascular Systemmentioning
confidence: 99%
See 3 more Smart Citations